Chemosensitivity Testing in Oncology. - Schlag, P. M (Springer Berlin Heidelberg, 2003)
Recent Results in Cancer Research 161 -- Chemosensitivity Testing in Oncology -- Copyright -- Preface -- Contents -- Principal Authors -- In Vitro Drug Testing Methods: Recent Developments 1 -- Luminescence Applications for Chemotherapeutic Drug Development -- The Use of the MTT Assay to Study Drug Resistance in Fresh Tumour Samples -- Chemosensitivity Testing of Human Tumors Using Si-sensor Chips -- Multiparametric Sensor Chips for Chemosensitivity Testing of Sensitive and Resistant Tumor Cells -- Development of a New In Vitro Chemosensitivity Test Using Collagen Gel Droplet Embedded Culture and Image Analysis for Clinical Usefulness -- In Vitro Chemosensitivity Testing of Hematological Cancer Patients: Detection of Ornithine Decarboxylase -- Tumor Chemosensitivity Assays: Evaluation of In Vitro Results 2 -- The Chemosensitivity Profile of Retinoblastoma -- Chemosensitivity Testing in Malignant Melanoma -- Human Melanoma: Drug Resistance -- Cisplatin, Doxorubicin and Paclitaxel Induce mdr1 Gene Transcription in Ovarian Cancer Cell Lines -- Clinical Relevance of Tumor-Directed Therapy 3 -- Chemosensitivity Testing as an Aid to Anti-Cancer Drug and Regimen Development -- Assay-Assisted Treatment Selection for Women with Breast or Ovarian Cancer -- Chemosensitivity Testing in Gynecologic Oncology - Dream or Reality? -- Treosulfan in the Treatment of Metastatic Melanoma: From Chemosensitivity Testing to Clinical Trials -- Chemosensitivity Testing and Test-Directed Chemotherapy in Human Pancreatic Cancer -- Clinical Significance of Cellular Drug Resistance in Childhood Leukemia -- ATP Chemosensitivity Testing in Ovarian and Breast Cancer: Early Clinical Trials -- Chemosensitivity Testing - Present and Future in Japan -- Subject Index.
Description based on publisher supplied metadata and other sources